Educator Performance on Learning Motivation of Students SMA Plus Al Azhar Jember Learning Year 2022/2023 - Lia Zannuba Adilah; St. Rodliyah; Ubaidillah Ubaidillah (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Because teachers become facilitators and motivators who can serve, guide, and encourage students to achieve expected success and provide simple learning opportunities to students so that they can complete their education in a comfortable atmosphere, teachers play an important role in education. full of levity. Internal motivation creates, ensures continuity, and directs learning to achieve anticipated goals through motivation. Learning activities cannot be completed without motivation. The formulation of this research problem is in line with the phenomenon studied earlier, namely that teacher performance (X) and learning motivation (Y) are affected. This study uses product moment, a quantitative descriptive method, in testing data validity and to find data reliability. The alpha formula is used to find the reliability of the data. Test the hypothesis using the F test, and the T test using a simple linear regression model. A total of 190 educators and class XI female students from SMA Plus Al Azhar Jember participated in the study. Researchers used questionnaires to measure student learning motivation and teacher performance to measure variables. After analyzing the data collected from the research findings, it was determined that (1) the performance of educators at SMA Plus Al Azhar Jember was included in the sufficient category (88%), (2) student learning motivation at SMA Plus Al Azhar Jember was very good (86%), and (3) educator performance affected student learning motivation (57%). After analyzing the data collected from the research findings, it was determined that (1) the performance of educators at SMA Plus Al Azhar Jember was included in the sufficient category (88%), (2) student learning motivation at SMA Plus Al Azhar Jember was very good (86%), and (3) educator performance affected student learning motivation (57%)